THE EVALUATION OF CARE EFFORTS OF CARER STAFF WORKING IN CARING HOUSES FOR THE DISABLED BY GENDER (Third Sector Social Economic Review, 2023)
Gender is a phenomenon that takes place at the extreme points of our lives, and it also appears in the issue of care work. Domestic labor (that is, care work) and care work in the public sphere are both similar jobs and come out as concepts that meet each other. The aim of this research is to analyze the care work given by the caregivers in terms of gender. In this study, qualitative research method was used and semi-structured interview form was used to collect data. Content analysis was used to evaluate the data. As a result of the research conducted with 16 caregiver personnel, it was determined that female participants were more consumed than male participants and their gender had an effect on this situation.
Keywords: Gender; Domestic Labor; Care; Care Labor; Disabled Care